The Monitoring System for Water Quality Based on The Internet of Things (IoT) and Uses A TDS Sensor - Zafi, Ali; Saputra, Bagus Dwi; Bianto, Mufti Ari (Indonesian Journal of Engineering, Science and Technology, 2024)
This research focuses on designing an Internet of Things (IoT)-based water quality monitoring system for aquaculture ponds, utilizing Total Dissolved Solids (TDS) sensors and the ESP32 microcontroller. The system is developed to monitor water quality in real-time by measuring the concentration of dissolved solids in the pond water. Data from the TDS sensor is collected by the ESP32 microcontroller, which is connected to a WiFi network and subsequently transmitted to the cloud, where it is displayed on a website. The study shows that the system can categorize water quality into three statuses: safe, alert, and poor. These categories are based on predefined TDS threshold values. Daily collected data is processed to provide accurate information on water quality status. This system enables continuous monitoring, facilitating pond management. Users can easily access data through a web page that presents information in an easily understandable format. The research demonstrates the effectiveness of using the ESP32 microcontroller and TDS sensors in an IoT-based monitoring application, as well as the system's capability to provide clear and timely indications of water quality status. Keywords--  ESP32 Microcontroller; Total Dissolved Solids (TDS); Water Quality Sensor